Bio-electrocatalytic dechlorination of 2, 4-dichlorophenol. Effect of pH and operational configuration. (20th January 2021) - Leon-Fernandez, Luis Fernando; Rodrigo, Manuel Andrés; Villaseñor, José; Fernandez-Morales, F.J.
Highlights: Bioelectrochemical systems dechlorinate 2, 4-DCP at mild operating conditions. MFC mode allowed simultaneous power generation and dechlorination. Dechlorination kinetics was enhanced at acidic conditions at the cathode. Electroreductive dechlorination was further enhanced under MEC mode. Phenol, the final dechlorinated product, was further hydrogenated under MEC mode. Abstract: Bioelectrochemical systems (BESs) are regarded as effective green technologies for wastewater treatment, with low associated energy costs. This work studies the influence of the cathode pH and operational mode, as microbial fuel cell (MFC) or microbial electrolysis cell (MEC), on the electrocatalytic hydrodechlorination (ECH) of 2, 4-dichlorophenol (2, 4-DCP) in an abiotic cathode. When operating as MFC, the results showed that more acid cathode pH enhances the ECH reactions. Practically a total dechlorination was obtained after 72 h at cathode pH=5, whereas only an 88% dechlorination was obtained at pH=7. Also, ECH was further enhanced by operating under MEC mode, where the cathode was poised towards more negative potentials and higher current densities were achieved. The MEC presented a faster kinetics, reaching an 81% of dechlorination after 24 h of operation in batch mode and the full dechlorination after 48 hours. Additionally, when operating as MEC, the phenol obtained after the dechlorination reaction was further hydrogenated to cyclohexanone under these mild operating conditions, which would drastically reduce the toxicity of the effluent. Graphical abstract: Image, graphical abstract